PENGARUH PENGAWASAN INTERNAL, REFORMASI BIROKRASI, TERHADAP KINERJA APARATUR SIPIL NEGARA MELALUI PELAKSANAAN GOOD GOVERNANCE - Sanja Bernia, Ernis; Supriyadi, Edy; Tabroni (SEKOLAH PASCASARJANA PRESS, 2017)
The reform of the bureaucracy keeps real rolling fields of government activity, development and civic services, with the purpose of creation of efficiency and effectiveness in accordance with the demands of excellent service to the community. Efforts to bring about good governance (good governance) has become a priority of the Government's policy of Cabinet work. This research was conducted to find out the influence of internal oversight towards the implementation of good governance, know the influence of the reform of the bureaucracy towards the implementation of good governance, knowing the influence on performance of internal oversight ASN, know the influence of the reform of the bureaucracy, against the performance of ASN, know the influence of the reform of the bureaucracy, towards good governance. The sample in this study is taken by using the data collection method called the purposive sampling. The number of samples used IE as much as 200 respondents. The data obtained were analyzed using analysis of PLS (Partial Least Square) via software SmartPLS. The results showed that internal oversight had a positive but not significant toward good governance, reform of the bureaucracy has a positive and significant relationship towards good governance, internal oversight have a positive relationship but not significantly to the performance of the bureaucratic reform has relationships ASN positively and significantly to the performance of ASN, good governance has a positive and significant relationship towards the performance of ASN.